Functional Walking Activity After Combined Russian Current and Quadriceps Bench Exercise in Knee Osteoarthritis - Reza Oliverdy; Siti Munawarah; Riri Segita; Riyana Husna (Jurnal Kesehatan Terpadu, 2026)
Osteoarthritis is a degenerative joint disease characterized by damage to hyaline cartilage, increased subchondral bone thickness, bone sclerosis, osteophyte growth at the joint margins, and muscle weakness around the joint, which can cause limitations in functional activities, especially walking. This study aims to determine the effect of Russian Current combined with Quadriceps Bench Exercise on improving functional walking activity in patients with knee osteoarthritis at Dr. Drs. M. Hatta Bukittinggi Brain Hospital. This study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 11 respondents selected using purposive sampling techniques in accordance with the inclusion and exclusion criteria. The intervention was administered for 4 weeks with a therapy frequency of twice per week. Functional walking activity was measured using the Lequesne Index before and after the intervention. The results showed that the average functional walking activity before the intervention (pretest) was 5.91 with a standard deviation of 1.446, while after the intervention (posttest) it was 4.82 with a standard deviation of 1.471. The results of the statistical test using a paired t-test showed a p-value = 0.000 (p < 0.05), which means that there was a significant effect of the Russian Current combined with Quadriceps Bench Exercise on improving functional walking activity in patients with knee joint osteoarthritis.